2005
DOI: 10.1079/pns2005424
|View full text |Cite
|
Sign up to set email alerts
|

School- and family-based interventions to prevent overweight in children

Abstract: There have been only a few controlled studies on the prevention of overweight and obesity in children and adolescents. These studies differ in relation to strategy, setting, duration, focus, variables of outcome and statistical power, and therefore do not allow general conclusions to be made about the value of preventive measures. All school-based interventions aimed at the prevention of overweight and obesity show some improvement of health knowledge and healthrelated behaviours. Short-term effects on nutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
7

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 31 publications
0
54
0
7
Order By: Relevance
“…A difference between the groups was seen in the upper distribution of BMI and TSF at T1 so that there was a small but beneficial effect regarding the prevalence of overweight: it increased by a factor 2.2 and 2.0 in the nonintervention and intervention group, respectively. 24 The 4-y-incidence of overweight was reduced in the intervention group (36.5 vs 41.7% respectively). Comparing boys and girls, the effect was only seen in girls.…”
Section: Prevalence and Determinants Of Overweightmentioning
confidence: 86%
“…A difference between the groups was seen in the upper distribution of BMI and TSF at T1 so that there was a small but beneficial effect regarding the prevalence of overweight: it increased by a factor 2.2 and 2.0 in the nonintervention and intervention group, respectively. 24 The 4-y-incidence of overweight was reduced in the intervention group (36.5 vs 41.7% respectively). Comparing boys and girls, the effect was only seen in girls.…”
Section: Prevalence and Determinants Of Overweightmentioning
confidence: 86%
“…Entretanto, a aplicação de programas contínuos de educação nutricional desde a infância parece ser a melhor maneira de se tentar reverter o quadro de consumo alimentar inadequado 22 . O presente estudo corrobora essa ideia, apontando mudanças significantes no consumo dos escolares intervencionados, como a redução no consumo de suco artificial.…”
Section: Discussionunclassified
“…Other studies have found exactly the opposite: higher SES being associated with greater treatment success. 21,34,35 Perhaps, the treatment evaluated in the current study was particularly easily accessible and not pedantic by nature. Further research is necessary to find out from what components in treatment different SES groups profit.…”
Section: Discussionmentioning
confidence: 99%